Analisis Wacana Kritis Pada Konten Youtube Malaka Project "Generalis VS Spesialis, Siapa Yang Menang Di Dunia Kerja" - Lukman Prasetya Nugraha; Muhammad Fadeli; Ratna Setyarahajoe (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study analyzes the critical discourse of a YouTube video from the Malaka Project channel titled "Generalist vs Specialist: Who Wins in the Job Market?". The analysis responds to rapid changes in the job market driven by advancements in artificial intelligence (AI). The method used is Teun A. van Dijk’s critical discourse analysis, examining both the macro and micro text structures as well as social cognition and the social context of the discourse. The findings reveal that the video constructs a pro-generalist narrative as a solution to the dynamic challenges of the job market, particularly in Indonesia. The use of simple and accessible language serves as a key strategy to convey the message in a systematic and organized manner, influencing viewers’ perceptions and attitudes. The content not only delivers information but also shapes an ideology emphasizing the importance of adaptability in facing changing times. It critiques the old paradigm that overly values formal education credentials while neglecting practical skills development and work flexibility. Therefore, the Malaka Project video functions as both an educational medium and an agent for shaping social discourse relevant to current societal and labor market needs.